Smallholder Farmers’ Uptake of Initiatives to Mitigate the Livelihood Effects of Changing Land Use Patterns in the Abokobi Municipality - Nyarko, E.N.A. (University of Ghana, 2016)
Small-holder farmers in the urban and peri-urban areas have become very vulnerable to land use change patterns due to rapid increase in population and urbanization. Farmlands are gradually being converted to residential facilities, posing significant threat to the livelihood of farmers who depend on such lands. Land use change at Abokobi dates back to the 2004, but the phenomena became more pronounced in 2008 when the Ga East District attained municipal status. With support from the Department of Agriculture, small-holder farmers in Abokobi were offered alternative livelihood programmes in livestock and high yielding crop varieties and non-traditional farming practices under the Heifer Project. This study sought to assess the extent of farmer uptake of the alternative livelihood support programmes. Mixed approaches of qualitative and quantitative methods were used to engage 100 farmers in a survey whiles 12 others were engaged in a focus group discussion. Three project officials were engaged in an in-depth interview. The findings revealed that farmlands were increasingly being sold to estate developers leading to a reduction in farm size, output and income. Of the 100 farmers in the survey, 49 were under the Heifer project, 33 were engaged in their own alternative livelihood activities and 18 were not engaged in any livelihood activity. Those with successful uptake of the Heifer programme had higher income relative to those who did not adopt. The factors that influenced successful uptake of the alternative livelihood programmes were expectation, incentive and benefits from the programme, educational level, age and household size of farmers. The study recommended that providers should engage farmers before introducing them to alternative livelihood programmes, proper and efficient planning of urban areas with much consideration for the preservation of space for agriculture should be considered and continuous education of farmers in peri-urban areas not to depend only on farming.
Thesis(M.A)-University of Ghana, 2016
Keywords: Smallholder Farmers’ Uptake; Livelihood Effects; Land Use Patterns